EVALUASI GERAKAN MORAL BERSIH DALAM IMPLEMENTASI GCG di KEDAI MIE AYAM YUMIE SOLO MENURUT PANDANGAN KRISTIANI - Puspitasari, Laura Dwi; Adristi, Erastus Christa; Nany, Magdalena; Rumekso, Ayub Widhi; Tjahjono, Pramadi; Nany, MMagdalena (TONGKONAN: JURNAL PENGABDIAN MASYARAKAT, 2024)
Good governance is one of the keys to a company's success to grow in the long term. One of the first steps that can be taken by companies in implementing Good Corporate Governance (GCG) is through the Clean, Transparent and Professional (BTP) Moral Movement. As a newly established business, the manager of the YuMie chicken noodle shop needs to get used to the implementation of a clean moral movement that contains the values of integrity, credibility, honesty and anti-corruption. The data collection techniques used were interviews and observations. Shop managers have shown their seriousness and commitment in implementing the clean moral movement, although there is no formal safe and confidential channel for employees to report dishonesty or ethical violations, does not have a clear written policy on the prohibition of corruption, collusion and nepotism, nor does it have an effective formal oversight system to detect and prevent corrupt practices, collusion and nepotism. The absence of a formal policy results in a less structured decision making process and does not always involve all stakeholders.